The Effect of Diet and Cardiovascular Risk on Ovarian Aging in Cynomolgus Monkeys (Macaca fascicularis) - Appt, Susan E. (2010)
OBJECTIVES: To determine the relationships among dietary protein source, cardiovascular risk, reproductive hormones and ovarian aging. METHODS: Adult female cynomolgus monkeys (Macaca fascicularis) were assigned randomly to one of two diets containing saturated fat and cholesterol, differing only by protein source: 1) casein-lactalbumin (n = 29) or 2) soy protein with isoflavones (n = 32). Cardiovascular risk markers and reproductive hormones were measured at baseline and after 32 months of treatment, at which time the ovaries were removed, serially sectioned, and ovarian follicles counted in every 100(th) section. RESULTS: Casein-lactalbumin-fed monkeys had fewer primordial, primary, and secondary follicles (all p's <0.05) than did their soy-fed counterparts. AMH was significantly correlated with all follicle types (r's≥0.66, p's< 0.001) for casein-fed monkeys, and was significantly correlated with primary (r(soy)=0.47, p=0.005) and secondary (r(soy)=0.45, p=0.007) follicles in soy-fed monkeys. No significant associations were seen between any of the other reproductive hormones measured and follicle counts. Casein-lactalbumin-fed monkeys had a more atherogenic lipoprotein profile and increased atherosclerosis extent (p< 0.05), but despite these differences in cardiovascular risk between casein-lactalbumin- and soy-fed monkeys, none of the individual cardiovascular risk markers measured in this study explained the relationship between dietary protein source and follicle counts (linear regression, all p's>0.05). CONCLUSIONS: Diet influences the rate of follicular depletion in cynomolgus macaques; however, the mechanism for this effect remains undetermined.